2018
DOI: 10.1371/journal.pone.0204028
|View full text |Cite
|
Sign up to set email alerts
|

Genetic variants analysis of three dromedary camels using whole genome sequencing data

Abstract: Whole genome wide identification and annotation of genetic variations in camels is in its first steps. The aim of this study was the identification of genome wide variants, functional annotations of them and enrichment analysis of affected genes using whole genome sequencing data of three dromedary camels. The genomes of two Iranian female dromedary camels that mostly used to produce meat and milk were sequenced to 41.9-fold and 38.6-fold coverage. A total of 4,727,238 single-nucleotide polymorphisms (SNPs) an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 38 publications
5
17
0
Order By: Relevance
“…The heterozygote to homozygote SNP ratio in DC399 (1.75), DC408 (1.79), and Bac2 (1.82) was close, while this value was 3.77 for Bac1. This result was consistent with our previous work on the Iranian dromedary camel which showed higher heterozygosity in them [15]. Based on the microsatellite data, there is introgression between Bactrian and dromedary camels in Iran [6]; therefore, observing higher heterozygosity in a portion of the Iranian camel's population is not unexpected.…”
supporting
confidence: 92%
See 4 more Smart Citations
“…The heterozygote to homozygote SNP ratio in DC399 (1.75), DC408 (1.79), and Bac2 (1.82) was close, while this value was 3.77 for Bac1. This result was consistent with our previous work on the Iranian dromedary camel which showed higher heterozygosity in them [15]. Based on the microsatellite data, there is introgression between Bactrian and dromedary camels in Iran [6]; therefore, observing higher heterozygosity in a portion of the Iranian camel's population is not unexpected.…”
supporting
confidence: 92%
“…Annotation results revealed that most portion of the discovered variants throughout the genome of Bactrian camels (more than 88 percent) are located in the intergenic and intronic regions. Our results were consistent with these values for Iranian (87.7% for SNPs, 88.9% for INDELs) and African dromedary camels (88% for SNPs, 89.1% for INDELs; [15]).…”
supporting
confidence: 91%
See 3 more Smart Citations